Impacto das características clínico-epidemiológicas e microbiológicas sobre os custos do tratamento de úlceras do pé diabético - Batista, Julianne Soares Jardim Lacerda (2023)
Estimates from the International Diabetes Federation indicate that there are approximately 463 million people living with diabetes worldwide. About a third of these people may have diabetic foot in their lifetime, a major public health problem that directly contributes to the loss of quality of life. This study aimed to analyze how the clinical, epidemiological and microbiological characteristics impact the costs of treating diabetic foot ulcers (DFU) and to develop educational material to encourage self-care and prevention. The research was carried out in a tertiary hospital located in Vitória-ES. Demographic, clinical and microbiological data of each patient was carried out through their electronic medical records. Information related to the cost of each service was obtained from the financial sector of the hospital and included costs with hospitality services, procedures and physiotherapy, surgery, materials, medications (except antimicrobials), and antimicrobials. The patients were separated into two groups, low and high risk for adverse events (delayed healing, amputations and deaths), as established by the PEDIS Score. The elaboration of the prevention strategy was based on the creation of a script adapted for comics with more recent concepts and approaches regarding the care of the diabetic foot. Analysis of the impact of clinical and epidemiological variables on costs included 121 patients with DFU. The amputation rate among all patients was 64.46% and the high-risk group was six times more likely to have an amputation (OR= 6.01; 95% confidence interval = 2.23 -16.2). The median cost per hospital care was Int$13,503.35 (interquartile range (IQR) = 8,326.25 - 23,542.51). The cost of treating highrisk patients (median = Int$ 14,180.15; IIQ = 9,440.94 – 24,775.37) was 1.72 times higher than the cost of treating low-risk patients (median = Int$ 8,229.07; IIQ = 2,046.01 - 16,086.63) (p-value = 0.0003). Overall, surgeries and daily rates were the categories that most impacted final costs. Of the 121 patients, 97 had an infected ulcer and were eligible for the study of the impact of microbiological characteristics on costs. A total of 226 microorganisms were isolated from these infections and 68.14% were Gramnegative bacteria. The following were related to longer average length of stay and costs: polymicrobial infections (31.92 days; Int$ 21,755.92), infections caused by multidrug-resistant microorganisms (29.84 days; Int$ 20,219.99) and those caused by methicillin-resistant Staphylococcus aureus (30.25 days; Int$ 20,607.29). The cost of antimicrobials was significantly higher in cases of polymicrobial infections and in the presence of multidrug-resistant microorganisms. A book was produced “Zé, e esse pé? Uma história sobre pé diabético”, in comic book format, aimed at the general public and aimed at raising awareness about the prevention of diabetes and its complications. In conclusion, we demonstrate the high-cost burden of DFU treatment on the health system and identify features significantly related to higher costs. Understanding the areas that consume the most resources can help manage and direct them in an economically viable way. In addition, we observed that the microbiological profile, number of microorganisms isolated per wound and the antimicrobial resistance profile can directly influence the costs of treating diabetic foot infections. Given the findings of this study and the advancement of diabetes, we understand that materials such as the comic book can be good allies in the prevention and care of diabetes.